Perjanjian Pinjam Nama Perusahaan dalam Pelaksanaan Lelang Pengadaan Jasa Konstruksi Pemerintah Provinsi Aceh - Muhammad Isra; Ilyas; Adwani (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2018)
Article 87 paragraph (3) of Presidential Regulation No. 54/2010 concerning Procurement of Goods / Services, â€œproviders of goods / services are prohibited from dealing with side jobs with subcontracts to other parties, except for part of the main work to the provider of specialist goods / servicesâ€ the name of the company is still done. This research shall explain the responsibility of the company of individual construction service provider / business entity borrower nameof the company can not perform the work according to Presidential Regulation 54 Year 2010, rights and obligations of individual / business entity joining independent business, due to law of service provider company and individual / the borrowerâ€™s name if the work is not carried out accordingly, and the factors that cause the individual / business entity. The results indicate the responsibility of the company that is designated as a provider of construction services based on the work contract, the occupation of occupation in accordance with the employment contract by the borrower of the name of the company is the responsibility of the company that is run. Rights and obligations of Individuals / Business Entities that lease the name of the company providing construction services on the power of attorney. The legal consequences of a service provider company that is unable to carry out contracted work, termination letter, blacklist for 2 (two) years, due to law experienced by an individual / business entity in accordance with the employment agreement and power of attorney is to replace any losses that arise. Causes - factors causing it. There is no complete administrative requirements and penalties.